Research on Promotion Strategies for Financial Information Technology Innovation Products in Small and Medium-Sized Financial Institutions: Construction and Application of a Data-Driven Decision System - Zhang, Jin (Innovation in Science and Technology, 2025)
The rapid development of financial technology has positioned financial information technology innovation products as crucial tools in enhancing the efficiency of financial services, optimizing risk management, and improving customer experience. However, small and medium-sized financial institutions (SMEFs) face significant challenges in their digital transformation journey, including inadequate technological capabilities, substantial cost pressures, and concerns over data security and privacy. These challenges have impeded the widespread adoption of financial information technology innovation products. This study constructs a Data-Driven Promotion Decision System (DDPDS) to meticulously analyze the business requirements, operational models, and market trends of SMEFs, thereby devising a targeted promotion strategy. The research initially clarifies the characteristics of financial information technology innovation products and their current application status in SMEFs. Subsequently, the DDPDS is employed to conduct a precise analysis of SMEFs’ needs, and a differentiated promotion plan is proposed in conjunction with market trends.